(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2019)
The article summarized data on Pseudospiropes M.B. Ellis representatives, which have been poorly studied in Ukraine. Basing on the literature review and critical revision of specimens stored in the scientific mycological herbarium CWU (Myc), for Ukraine at least four species of this genus can begiver: P. simplex (Kunze ex Pers.) M.B. Ellis, P. nodosus (Wallr.) M.B. Ellis, P. josserandii (Bertault) Iturr. and P. obclavatus M.B. Ellis. Complete nomenclature characteristics, detailed descriptions, distribution in the world and Ukraine, substrate preferences and periods of sporulation of these species considering also the characteristics of the natural zones, where these fungi were found, are given below. The article contains dichotomic key and original illustrations of asexual morphs for all species. It was shown that the first find of Strossmayeria basitricha (Sacc.) Dennis in Ukraine (teleomorph Pseudospiropes simplex) was recorded by Albert Pilat while his expedition to Zakarpattia (sample PRM 149988). But in the monograph of J.Velenovsky it mentioned as a new for science species Gorgoniceps pilatii Velen. In more modern articles location of the sample is wrongly indicated as Czechoslovakia. Therefore information about this find has not been mentioned in the mycological publications dealt with fungi of Ukraine. The article gives a detailed analysis of taxonomic relevance of morphological criteria that traditionally are used for identification of twine-species P. josserandii and P. simplex. The majority of the Pseudospiropes samples from Ukraine are represented by anamorph, occasionally there are some apothecia at the same time with asexual sporulation. Therefore we are not able to use morphological criteria of sexual structures. It is proved that the thickness of the basal scar as a hallmark is unreliable because it depends on the maturity of spores. Now there is only one feature that allows identifying species P. josserandii and P. simplex in anamorph stage – wideness of the basal scar of the conidia. To assess the reliability of this criterion, it is necessary to carry out molecular phylogenetic analysis.